Simulation and control for VTOL UAV - Khoo, Yi Shao (Nanyang Technological University, 2021)
The demand for Vertical Take-Off and Landing (VTOL) Unmanned Aerial Vehicles (UAVs) has been growing due to the wide applications that this specific aircraft type can provide, regardless civil, military, or commercial use. VTOL technology is growing and there is no best configuration that fits all mission. This report documents the development of a Tilt-rotor VTOL UAV model, with focus on the aspect of flight controls autopilot application. A tiltrotor aircraft utilises the same set propulsive actuator to perform both vertical take-off and forward flight, thus reduces deadweight on aircraft. The preliminary design of the VTOL UAV was done using XFLR5 simulation to ensure aircraft stability and sufficient wing loading. Subsequently, flight controls are developed using PX4 autopilot flight stack for tilt rotors UAV and Pixhawk 4 Mini as the flight computer. Flight trials are conducted in conjunction with MATLAB Simulink 3DOF Simulations to evaluate the performance of the developed flight controls system and the flight capabilities of the VTOL UAV Model. In this project, yaw drift was restored during transition and the importance of blending both of elevons and motors for pitch control during transition was demonstrated.